Psychosocial Factors and Comorbidity Associated with Recovery in Bipolar Disorder - Daniel, Rapport; Denis, Lynch; Angele, McGrady; Dheeraj, Kaplish; Ron, McGinnis; Kary, Whearty (Journal of Depression And Therapy, 2016)
Bipolar disorder (BD) is a chronic psychiatric illness impacting patient functioning and quality of life. Medication produces improvement in many patients and remission in some, but there is minimal understanding about why some patients improve and others do not. Our goal was to identify demographic, psychosocial and comorbid variables associated with outcomes in BD. Charts of 121 outpatients treated with medication and supportive psychotherapy were reviewed. Forty four percent attained euthymia for 12 months while 56% did not. Poorer outcome was associated with economic stress, missed appointments, life stress, and presence of pain (p < 0.05). Those employed were more likely to improve (p < 0.02). Patients with BP-II reported more frequent life stressors, headache and use of alcohol (p <0.05) and were less likely to achieve euthymia than BP-I. Gender, education, and co-morbid medical illness did not affect results. Our findings suggest that poorer outcome is related to psychosocial factors. Increased attention to these variables may increase providers’ ability to manage challenging patients with BD.
Keywords: bipolar disorder; psychosocial factors; life stress; outcome